2011
DOI: 10.1007/s11430-011-4189-y
|View full text |Cite
|
Sign up to set email alerts
|

Early cretaceous extensional structures in the Liaodong Peninsula: Structural associations, geochronological constraints and regional tectonic implications

Abstract: Various extensional structures, e.g., half grabens, detachment faults, and metamorphic core complexes, were formed in the Liaodong Peninsula. There are two metamorphic core complexes (mcc's) in the western part of the Peninsula, i.e. the Liaonan mcc and the Wanfu mcc. They share the same lower plate and constitute a conjugate mcc pair. The Dayingzi detachment fault system and the three half grabens are exposed in the central and eastern parts, respectively. U-Pb dating of zircons from syntectonic plutons in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…Traynor and Sladen, 1995;Chough et al, 2000;Mazukabzov et al, 2006;Erdenetsogt et al, 2009;Andryushchenko et al, 2010;Chough and Sohn, 2010;Metelkin et al, 2010;Daoudene et al, 2011) and several national and international conferences have been organized on this topic, the tectonic evolution and geodynamics of the different tectonic events are still hotly debated (e.g. Davis et al, 2001;Darby and Ritts, 2002;Liu et al, 2005;Lin et al, 2007Lin et al, , 2008Vergely et al, 2007;Davis and Darby, 2010;Liu et al, 2011;Zhang et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Traynor and Sladen, 1995;Chough et al, 2000;Mazukabzov et al, 2006;Erdenetsogt et al, 2009;Andryushchenko et al, 2010;Chough and Sohn, 2010;Metelkin et al, 2010;Daoudene et al, 2011) and several national and international conferences have been organized on this topic, the tectonic evolution and geodynamics of the different tectonic events are still hotly debated (e.g. Davis et al, 2001;Darby and Ritts, 2002;Liu et al, 2005;Lin et al, 2007Lin et al, , 2008Vergely et al, 2007;Davis and Darby, 2010;Liu et al, 2011;Zhang et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Combining structural and microstructural analysis and geothermobarometry data, it is suggested that the Zhaotun monzogranite emplaced and deformed at a relatively deep crustal level during detachment faulting. Liu et al (2011Liu et al ( , 2013. 40 Ar/ 39 Ar ages of hornblende, muscovite, biotite and K-feldspar are from Yang et al (2007a), Yang et al (2007b) and Lin et al (2011) Wu et al, 2005;Guo et al, 2004;Ji et al, 2009;Liu et al, 2013).…”
Section: Lower Plate Intrusionsmentioning
confidence: 97%
“…The zircon U-Pb (SHRIMP and LA-ICPMS) ages of the plutonic rocks range from 130 ± 5 Ma to 113 ± 2 Ma Wu et al, 2005). However, the Zhaofang granodioritic porphyry, was suggested to be a typical postkinematic intrusion ), but the others were suggested to be syn-kinematic intrusions during regional extension Liu et al, 2011Liu et al, , 2013Wu et al, 2005). In addition, the trachy-dacite at Yuhuangding in the supradetachment basin was also related to the formation of the basin during extension.…”
Section: Lower Plate Intrusionsmentioning
confidence: 99%
See 2 more Smart Citations